Account Trading As A Form Of Money Laundering - Ritonga, Arifin Said (Inspiring Law Journal, 2024)
In practice, buying and selling bank accounts is often used to hide or disguise the origin of funds that are the result of criminal acts, thus obscuring the financial trail and complicating law enforcement efforts. In cases of money laundering, buying and selling bank accounts can be categorized as active and passive money laundering. The party selling the account can be categorized as a passive money launderer because the perpetrator receives or controls assets that are the result of criminal acts. Conversely, the party buying the account can be categorized as an active money launderer because the perpetrator takes active actions such as placing, transferring, spending, or disguising the origin of assets that are the result of criminal acts. Due to the rampant buying and selling of accounts, the OJK has ordered banks to block a number of accounts used in illegal activities, fraudulent transfers by pretending to buy and sell goods, including online gambling. This refers to several provisions in Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector. However, the absence of regulations on penalties and prohibitions regarding the practice of buying and selling accounts in the TPPU Law makes it difficult to impose criminal liability on the perpetrators. Because the principle of legality in criminal law stipulates that a crime cannot be punished except based on the principle of legality, the criminal provisions of the law that existed before the crime was committed. Thus, there needs to be a provision or change to the rules that can accommodate the sale and purchase of this account. The practice of buying and selling bank accounts has not been clearly and in detail regulated in Law No. 8 of 2010 concerning the Prevention and Eradication of Criminal Acts of Corruption